A review of the genera Diastictus Mulsant, 1842, Pleurophorus Mulsant, 1842, Platytomus Mulsant, 1842 and Pararhyssemus Balthasar, 1955 (Coleoptera: Scarabaeidae: Psammodiini) of Russia and adjacent territories - I.V. Shokhin (Кавказский энтомологический бюллетень, 2006)
The review of the genera Diastictus Mulsant, 1842, Pleurophorus Mulsant, 1842, Platytomus Mulsant, 1842 and Pararhyssemus Balthasar, 1955 of Russia and the adjacent countries is given. Distribution and characteristic features of 10 species are given. New synonymy is established: Platytomus tibialis (Fabricius, 1798) = Pleurophorus laevistriatus jailensis Apostolov et Maltzev, 1986, syn. n. Pleurophorus arabicus Pittino, Mariani, 1986 is recorded as new for the fauna of Russia, Pararhyssemus coluber (Mayet, 1887) – as new for the fauna of Middle Asia